If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -2 = 10 + 3b Reorder the terms: -2 + 6b = 10 + 3b Solving -2 + 6b = 10 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. -2 + 6b + -3b = 10 + 3b + -3b Combine like terms: 6b + -3b = 3b -2 + 3b = 10 + 3b + -3b Combine like terms: 3b + -3b = 0 -2 + 3b = 10 + 0 -2 + 3b = 10 Add '2' to each side of the equation. -2 + 2 + 3b = 10 + 2 Combine like terms: -2 + 2 = 0 0 + 3b = 10 + 2 3b = 10 + 2 Combine like terms: 10 + 2 = 12 3b = 12 Divide each side by '3'. b = 4 Simplifying b = 4
| -9(2-8)+4x+10=229 | | 8=3-5x | | 1+6x+5x=100 | | 7x(2+8)= | | -y=3x+6 | | -y^3x-2x^4y^3= | | 2y^2+4y-1=7y^2-7y+1 | | 378=(15+x)(12+x) | | d+99999999999999999990=999999999999999999 | | x+(x*4)=4 | | 12-2x=3x+22 | | 3.4c-1.2c=8.8 | | x-4/3+1=7/6 | | 5m+18=15-24-4m | | -k+2=-2k-2-4 | | 9(b+7)=9(b-5) | | 1(23)(-18)(2)= | | Y-39=-39 | | 8k-4k-8= | | (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 | | 83-x=93-2x | | .8(x+4)-.3x=1.7 | | n*2-12=34 |